Remarkably high prevalence of overuse-related knee complaints and MRI abnormalities in youth competitive alpine skiers: a descriptive investigation in 108 athletes aged 13–15 years. Issue 1 (30th May 2020) - Fröhlich, Stefan; Peterhans, Loris; Stern, Christoph; Frey, Walter O; Sutter, Reto; Spörri, Jörg
Abstract : Background/aim: Competitive alpine skiing is known to be associated with a high risk of traumatic knee injuries. However, little is known about the exact prevalence of knee overuse injuries and their associations with structural changes, particularly in youth skiers. Accordingly, the aim of the present study was to describe the overuse-related knee complaints and MRI abnormalities in a cohort of youth skiers around the growth spurt. Methods: 108 youth competitive alpine skiers aged 13–15 years were examined using an MRI of both knees, an interview on existing knee complaints and a physical examination. As a common baseline for these assessments, skiers were prospectively monitored by the use of the Oslo Sports Trauma Research Centre questionnaire on health problems over a period of 12 months preceding the major investigations. Results: 88.0% of the youth skiers showed at least one MRI abnormality in the knees. The most frequent findings were distal femoral cortical irregularities (63%), focal periphyseal oedema (FOPE) zones (25.0%) and cartilage lesions (18.5%). 47.2% of all skiers suffered from at least one overuse-related knee complaint during the 12 months preceding the MRI examination, mostly at the distal and proximal patellar tendon. However, despite a certain association with corresponding MRI abnormalities, the sensitivity of an MRI-based detection of such complaints was strongly limited. Conclusion: Youth competitive alpine skiers suffer from a remarkably large number of knee overuse injuries. Accordingly, an effective prevention strategy should include a systematic screening of clinical complaints, ideally already starting around the growth spurt.